The Development of Integrated Thematic Module of Thw Quran and Al Hadits on Theme 7 to Support Indepensent Learning at Grade 1 SDIP Daaruth Thullab 02 Koto Salak - Novri Asmara, Dwi; Mulia Rizki, Elvira (TOFEDU: The Future of Education Journal, 2022)
This research is motivated by the lack of integrated thematic modules of the Al-Qur'an and Al-Hadith so that students still do not understand the material in ordinary books. Efforts to overcome these problems are necessary to develop integrated modules to assist students in the learning process. The purpose of this study was to produce a valid, practical and effective theme 7 integrated module of the Al-Qur'an and Al-Hadith. This type of research is Research and Development (R&D) research using the ADDIE model which consists of 5 stages (Analyze, Design, Development, Implementation, and Evaluation). The test subjects were grade 1 students at SDIP Daaruth Thullab 02 Koto Salak using the Al-Qur'an and Al-Hadith Integrated Module. The results of the validation carried out by three validators obtained an average validity value of 87% with a very valid category. In the sense that the integrated Al-Qur'an and Al-Hadith modules are suitable for use by students. The results of the practicality value of the homeroom teacher's response questionnaire obtained an average of 84% in the very practical category. In the sense that the module is easy to use by students. The results of the effectiveness value obtained an average of 83% with the effective category. In the sense that the module has a good impact and helps students achieve learning goals, as well as supports the concept of independent learning